ANALYSIS OF DOMESTIC PRODUCTION IN RELATION TO THE DEMAND AND SUPPLY OF GRAPES IN ROMANIA - Daniela Nicoleta BĂDAN; Ionut Laurentiu PETRE (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Venturia inaequalis is a known pathogen for long time as causing apple scab disease or black spots. The extent of the disease expression highly depends on apple cultivars, the presence in orchards of host plants of the pathogen, climatic conditions and agricultural practices. Today it becomes more important to broaden the access to more diverse genetic resources in order to improve the breeding programs including for apple varieties. The scope of this article is to analyse how much are affected apple trees by apple scab in the traditional orchards of Sibiu, Fântânele. These orchards are maintained without any pesticides, only traditional practices being applied for more than 30 years. Therefore, we consider that this hot-spot of apple diversity can be a valuable pool gene for further breeding programmes in Europe. Based on our results we can conclude that 'Belle de Boskoop’, 'Winter Pearmain’, 'London Pepping’, 'Batul Alma’, 'Edelborsdorfer’, 'Boiken’, 'Yellow Bellflower’, 'Reinette Ananas’ and 'Reinette Baumann’ are among the best resisting cultivars against this disease. 'Golden delicious’ is obviously the most susceptible apple cultivar against V. inaequalis.